2017
DOI: 10.21873/anticanres.11685
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Preoperative Neutrophil-to-Lymphocyte and Platelet-to-Lymphocyte Ratios on Survival in Patients with Extrahepatic Cholangiocarcinoma

Abstract: High preoperative PLR was an independent predictor of poor prognosis for patients with ECC who underwent resections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 24 publications
3
40
0
Order By: Relevance
“…After screening the titles and abstracts carefully, 75 articles were excluded. Finally, a total of 9 studies were included in the meta-analysis [ 13 15 , 19 – 24 ]. All of the included studies were retrospective observational cohorts.…”
Section: Resultsmentioning
confidence: 99%
“…After screening the titles and abstracts carefully, 75 articles were excluded. Finally, a total of 9 studies were included in the meta-analysis [ 13 15 , 19 – 24 ]. All of the included studies were retrospective observational cohorts.…”
Section: Resultsmentioning
confidence: 99%
“…However, controversies still exist regarding the prognostic value of NLR in cholangiocarcinoma [8-12, 26]. Likewise, conflicting survival data are present regarding PLR in cholangiocarcinoma patients [10, 12, 26, 27]. A possible cause of the conflicting results regarding the prognostic significance of NLR and PLR in cholangiocarcinoma is that the reported cutoffs of these indices were different.…”
Section: Discussionmentioning
confidence: 99%
“…Biomarkers of inflammation, such as NLR or PLR, have been associated with the prognosis of patients with various cancers7, 8 and have specifically been shown to be predictive markers of postoperative prognosis in gastric cancer,14 cholangiocarcinoma,15 hepatocellular carcinoma,8 and primary lung cancer 16. Some studies have reported that host‐derived inflammation, immune response, and coagulation status play important roles in tumor growth, invasion, angiogenesis, and metastasis 17…”
Section: Discussionmentioning
confidence: 99%